2016
DOI: 10.1016/j.jtho.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Secreted from Cancer-Associated Fibroblasts Mediates Chemoresistance in NSCLC by Increasing Epithelial-Mesenchymal Transition Signaling

Abstract: IL-6 from CAFs enhanced EMT in NSCLC cells. IL-6 may contribute to maintenance of a paracrine loop that functions as part of the communication between CAFs and NSCLC cells, resulting in chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(180 citation statements)
references
References 35 publications
5
174
1
Order By: Relevance
“…has also demonstrated that increased osteoblast-derived IL6 promotes tumor cell seeding and bone metastases in a model of breast cancer cells injected in the arterial circulation [42]. IL6 is a pleiotropic cytokine, which is secreted from several cell types, including CAFs and plays a crucial role in the expansion of cancer stem cells [43, 44] as well as in the proliferation potential of CAFs [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…has also demonstrated that increased osteoblast-derived IL6 promotes tumor cell seeding and bone metastases in a model of breast cancer cells injected in the arterial circulation [42]. IL6 is a pleiotropic cytokine, which is secreted from several cell types, including CAFs and plays a crucial role in the expansion of cancer stem cells [43, 44] as well as in the proliferation potential of CAFs [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity is related to the density of specific stromal cells into TIM as well [27]. It has been reported that cancer-associated fibroblasts (a subset of stromal cells) secrete IL6 that enhances epithelial-to-mesenchymal transition changes in NSCLC cells: this transformation results in increased chemoresistance and worse outcome [28]. Thus, it is not surprising that higher levels of chemokines secreted by TIM (such as IL6 that increases also plasmatic CRP levels) are associated with worse NSCLC prognosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is now recognized as one of the most ubiquitously expressed and dysregulated cytokines in cancer, with increased expression found in multiple cancers (Becker et al, 2004; Fulciniti et al, 2009; Okamoto et al, 1997; Qu et al, 2015; Salgado et al, 2003). This cytokine has also been shown to induce mesenchymal features in cancers of the cervix (Miao et al, 2014), prostate (Shiota et al, 2013), lung (Shintani et al, 2016), and head and neck (Yadav et al, 2011), among others. Sullivan and colleagues (Sullivan et al, 2009) showed that exposure to exogenous IL-6 repressed E-cadherin expression in breast cancer cells, and ectopic expression resulted in a mesenchymal-like phenotype and gene expression pattern both in vitro and in vivo .…”
Section: Blocking and Reverting Tumor Mesenchymalizationmentioning
confidence: 99%